Performance of the doulas during the pregnancy-puerperal cycle: a literature review (Research, Society and Development, 2020)
The objective of the study was evidence the performance of doulas during the pregnancy-puerperal cycle according to the scientific publications and analyze how doula acts in the pregnancy-puerperal cycle according to scientific publications. This is a literature review study, at least integrative review method with a qualitative approach. Data collection was held in March 2020 in the databases of LILACS, BDENF and Medline. DECS descriptors and the Boolean AND operator were used. Included were primary studies that answer the research question, in English and Portuguese and Spanish and related to the theme in the years 2010 to 2019. As for the exclusion, literature review, criteria were duplicate texts, unavailable, thesis-type documents, mammography and that were not related to the theme. At the end of the sample, 12 articles were obtained, which were carefully analyzed. The study was divided into two categories in which the first shows how the doula works in the pregnancy-pregnancy cycle puerperal and the second deals with the humanization of childbirth and doula action. Against From the above, it is concluded that the performance of doulas during the puerperal pregnancy cycle is important in the monitoring of pregnant women, parturients and puerperal women, as it allows more humanized, quality, planned and individualized care.